2009
DOI: 10.1007/s10562-009-0086-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of NO x -Storage BaO/Al2O3 by Using Barium Peroxide as the Precursor of BaO

Abstract: Comparison of barium peroxide, Ba(OH) 2 and Ba(NO 3 ) 2 as the precursor of BaO for the preparation of NO x -storage BaO/Al 2 O 3 material was carried out. The as prepared materials were calcined at 550 and 800°C and characterized by N 2 physisorption, XRD, Raman and FT-IR spectroscopy. Measurements of the NO x storage performances of these BaO/Al 2 O 3 materials by NO 2 adsorption and NO x -TPD experiments showed that the use of barium peroxide as the precursor of BaO inhibited the formation of BaAl 2 O 4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…6). This silence of BaO in these XRD patterns is consistent with the earlier documentation 32,33 that BaO particles in NSR Pt-BaO/Al 2 O 3 catalysts were sufficiently small and were undetectable by a conventional laboratory powder XRD instrument. With a synchrotron XRD, however, Peden et al were successful in clearly detecting small and broad diffractions featuring BaO crystallites of ca.…”
Section: Origins Of the Al 2 O 3 Pct Effectsupporting
confidence: 91%
“…6). This silence of BaO in these XRD patterns is consistent with the earlier documentation 32,33 that BaO particles in NSR Pt-BaO/Al 2 O 3 catalysts were sufficiently small and were undetectable by a conventional laboratory powder XRD instrument. With a synchrotron XRD, however, Peden et al were successful in clearly detecting small and broad diffractions featuring BaO crystallites of ca.…”
Section: Origins Of the Al 2 O 3 Pct Effectsupporting
confidence: 91%
“…Inside a strongly interacting medium as in the description of nuclear matter, the momentum dependence of symmetry potential may lead to different values of the neutron/proton effective masses. The knowledge of the difference, also known as the nucleon effective mass splitting, is important for understanding not only level density of single particles, isovector Giant Dipole Resonance in nuclear structures and spectra of emitted particles in nuclear reactions but also many critical issues in astrophysics, such as heat capacity of matter, the neutron and proton chemical potential and their fraction [29,30,2,31,32,33,34,35,36,37]. There have been some efforts on constraining the nucleon effective mass splitting by analyzing the symmetry potenial U sym (ρ 0 , E) using nuclei optical potential data [2,33,38].…”
mentioning
confidence: 99%
“…[33] In a previous report, AuÀ Sn(II)/SAC shows higher activity and stability than that of AuÀ Cu(II)/SAC under same reaction conditions, indicating that the synergistic effect between Au 3 + and Sn(II) is stronger, whereas Sn(II) can effectively stabilize Au 3 + . [33,34] As shown in Figure 9, the characteristic reduction peaks of Cu 2 + in CuCl 2 /AC is appeared at approx-imately 352.7°C, [26,28,32] while the same peaks is observed at 525.6°C in case of Cu-MOF/AC, demonstrating the interaction between Cu 2 + and o-phthalic acid. The obvious reduction peak of Sn 2 + is observed at ca.487.5°C.…”
Section: Study Of the Catalytic Activementioning
confidence: 95%
“…[27] However, the coke deposition is due to the polymerization of acetylene and vinyl chloride during the hydrochlorination of acetylene. [25,28,29] Figure 7 displays the TG curve for Sn-MOF and Cu-MOF recorded between 25 and 800°C under nitrogen atmosphere. It can be observed that the mass loss up to 450°C were about 34.9% and 67.9% for Sn-MOF and Cu-MOF, respectively, suggesting that Sn-MOF featured better thermal stability than that of Cu-MOF.…”
Section: Performance and Stabilities Of Sn(ii)-or Cu(ii)-based Catalystsmentioning
confidence: 99%